NON TIMBER FOREST PRODUCT UTILIZATIONS AND AWARENESS OF SMALL-SCALE INDUSTRY DEVELOPMENT IN FOREST COMMUNITIES-A CASE STUDY IN EAST KALIMANTAN - Eli Nur Nirmala Sari (Indonesian Journal of Forestry Research, 2010)
A lack of livelihood to meet the needs has been one reason why forest communities have utilized non-timber forest products (NTFPs). For some communities living in or around forest areas, NTFPs have been a basic support for their small-scale industries, which could contribute to better income. This study focused on the utilization of NTFPs by forest communities and their awareness in terms of utilizing such products for handicrafts in small-scale industry. This study examined the NTFPs potentials, markets, and social benefits at the five villages in East Kalimantan, Indonesia. The villages-surveyed were Batu Lidung, Punan Bengalun, Sesua, Mendupo, and Seputuk which were located in and near forest areas managed by PT Intracawood Manufacturing as a forest concessionaire. The method used was Participatory Rural Appraisal Techniques, and the data collection was based on primary data and household survey. The result suggested that among the five villages, the most remote area was Punan Bengalun. Forest community of Punan Bengalun has started selling the handicrafts made from NTFPs only in the last few years. Among the five villages-sur veyed, the forest community in Seputuk tended to be more active in utilizing NTFPs for small-scale industry rather than those in four other villages. Awareness in utilizing the NTFPs had been mostly depended on factor of forest distance from the villages. People living close to the district capital (where there was a wider variety of employment opportunities) had less motivation to utilize NTFPs although there were available.